Queer Notions : New Plays and Performances from Ireland - Walsh, Fintan, Dr (Book collections on Project MUSE., 2010)
This collection is a record of some of the most important performative ideas and embodied interventions that have shaped queer culture and theatre and performance practice in Ireland in recent times. It includes plays, experimental performance documentation and a visual essay that reveal the creativity of culture.